GE_GERICHTE A/3212/2020 vom 21. Juni 2021 - GE Cour de justice (2021)
VALEUR FISCALE;REVENU DE LA FORTUNE IMMOBILIÈRE(DROIT FISCAL);VALEUR LOCATIVE;USUFRUIT;LEGS | LIFD.21.al1.letb; LIPP.24.al1.letb; LIPP.46; LIPP.48